2008
DOI: 10.1016/j.mar.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Intertwined coordination mechanisms in interorganizational relationships with dominated suppliers

Abstract: Contemporary business society shows many examples of industrial customers that manage their smaller, dependent suppliers by using bureaucratic mechanisms. The restrictions these control processes put on the suppliers" freedom to act have not been recognized in most studies within the field. The purpose of this article is to provide an understanding of how bureaucratic mechanisms interrelate with social mechanisms in coordinating interorganizational processes where the customer has a dominating role in the mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 36 publications
2
52
0
5
Order By: Relevance
“…For example, Ryan and Walsh () claim that hierarchical accountability structures obstruct cooperation. This claim is consistent with the conclusions in private sector research on how hierarchical control accountability influences inter‐organizational cooperation (Chenhall, ; Cäker, ; Håkansson and Lind, ). However, research on how inter‐organizational cooperation influences internal control systems in the public sector is scarce (Lacey et al, ; Shaoul et al, ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Ryan and Walsh () claim that hierarchical accountability structures obstruct cooperation. This claim is consistent with the conclusions in private sector research on how hierarchical control accountability influences inter‐organizational cooperation (Chenhall, ; Cäker, ; Håkansson and Lind, ). However, research on how inter‐organizational cooperation influences internal control systems in the public sector is scarce (Lacey et al, ; Shaoul et al, ).…”
Section: Introductionsupporting
confidence: 90%
“…This makes our setting especially relevant to further understanding of public sector inter‐organizational cooperation. Previous research has shown that such smaller (and dominated) actors may have limited influence on the control systems found in inter‐organizational cooperation (Cäker, ; Donada and Nogatchewsky, ; Cäker and Siverbo, ). Given the dominant actors’ control of governance issues, it is reasonable to assume that the dominated actors may sometimes clash with these control systems.…”
Section: Introductionmentioning
confidence: 99%
“…Groot and Merchant, 2000). Since, however, such informal controls (or social controls) may be rather fuzzy, some researchers argue they are best suited to situations where formal controls are difficult to use (Langfield-Smith, 2008;Ouchi, 1979) and where they may "fill the holes" left by formal controls in interorganizational settings (Cäker, 2008).…”
Section: Control Packagesmentioning
confidence: 99%
“…One inter-organizational arrangement that has been dealt with to a fairly large extent in the management control literature is outsourcing, i.e., when organizations contract out the manufacture of goods or the supply of services to other organizations (see, e.g., Frances and Garnsey, 1996;Van der Meer-Kooistra and Vosselman, 2000;Mouritsen et al, 2001;Langfield-Smith and Smith, 2003;Dekker, 2003Dekker, , 2004Dekker, , 2008Cooper and Slagmulder, 2004;Anderson and Dekker, 2005;Donada and Nogatchewsky, 2006;Cäker, 2008;Kraus and Lind, 2007;Free, 2008;Van der Meer-Kooistra and Scapens, 2008). However, most research on control in outsourcing relationships deals with private sector organizations and only to a lesser extent with public sector organizations (hereafter PSOs) (Broadbent and Guthrie, 2008;Samuel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%